ATM. in my room using recycled paper for painting a visual metaphor on the specialness in mundanity - Torres, Ma. Eliza F.; Imao, Abdulmari de Leon Jr.; Sta Ana, Mary Catherine P. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
Inescapable to human life, mundanity can be challenging to deal with by those who can be easily distressed by having a seemingly uninteresting life. My mundane moments often take place in a personal space - in my bedroom. I used recycled papers to form paintings that document the mundanity of my everyday life as lived out in a bedroom. In the process, my handmade paper-making from recycled paper also presented its special quality as a mundane material. The resulting paintings of objects and spaces within my bedroom, expose a sign of life, in their dullness and messiness. The produced paintings are an appreciation of life, valuing it not only in times of greatness but also in times of commonness and monotony. A monotonous life doesn't necessarily equate to an ineffective life, for something dull could still be meaningful.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 22-23
Keywords: Mundanity; Paper pulp painting; Intimism